1998
DOI: 10.1046/j.1365-2788.1998.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Clumsiness in autism and Asperger syndrome: a further report

Abstract: Clumsiness has been proposed as a diagnostic feature of Asperger syndrome (AS), a type of pervasive developmental disorder recently introduced in the ICD-10 and DSM-IV. However, the extent to which this symptom is specific to AS is not clear. To investigate this issue, we compared a sample of AS children with age- and sex-matched groups of children with autistic disorder and pervasive developmental disorder not otherwise specified (PDDNOS). Twelve subjects with AS (ICD-10/DSM-IV; 11 males; average age 11.4 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
198
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(215 citation statements)
references
References 12 publications
9
198
0
3
Order By: Relevance
“…For example, antibodies against glutamate receptors have been implicated in childhood seizure disorders, 112 a common comorbidity of ASD, 111,112 whereas antibodies against GABA recep- tors are associated with motor disorders, 113 which are widely reported in ASD. 114 Although antibodies for either receptor family have not been detected in ASD, numerous unknown targets for autoantibodies exist, and it is possible that these could include subunits of the GABA or glutamate receptors. Dysregulation of neurotransmitter systems could further drive aberrant immune responses in ASD and could thus point to possible targets for therapeutic intervention.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…For example, antibodies against glutamate receptors have been implicated in childhood seizure disorders, 112 a common comorbidity of ASD, 111,112 whereas antibodies against GABA recep- tors are associated with motor disorders, 113 which are widely reported in ASD. 114 Although antibodies for either receptor family have not been detected in ASD, numerous unknown targets for autoantibodies exist, and it is possible that these could include subunits of the GABA or glutamate receptors. Dysregulation of neurotransmitter systems could further drive aberrant immune responses in ASD and could thus point to possible targets for therapeutic intervention.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…Behavioural studies have shown that children with autism display a range of motor deficits [e.g., Ghaziuddin & Butler, 1998;Jansiewicz, Goldberg, Newschaffer, Denckla, Landa, & Mostofsky, 2006]. Green et al [2009] used a standardised motor battery, the Movement ABC [Henderson & Sugden, 1992], in a large, populationderived study of school-aged children with childhood autism and broader ASD, and found that 79% of the children with an ASD had definite motor impairments with a further 10% having borderline problems.…”
Section: Introductionmentioning
confidence: 99%
“…A risk with these studies is that the validity of their findings relies on initial, accurate categorization of participants; the lack of differentiation between AS and HFA, in the case of Manjiviona and Prior (1995), is likely to reflect invalid categorization based on the diagnostic manuals of the time. Some studies find greater motor deficits in individuals with HFA than those with AS (Behere, Shahani, Noggle, & Dean, 2012;Ghaziuddin & Butler, 1998;Green et al, 2009;Papadopoulos et al, 2012;Rinehart, Bellgrove, et al, 2006), others find the opposite picture (Iwanaga, Kawasaki, & Tsuchida, 2000), some find deficits of different types in both groups (Rinehart et al, 2001), and some find no statistical difference between groups (Jansiewicz et al, 2006;Noterdaeme, Mildenberger, Minow, & Amorosa, 2002). Some of these studies have very small samples (Behere et al, 2012;Ghaziuddin & Butler, 1998;Iwanaga et al, 2000;Rinehart, Bellgrove, et al, 2006;Rinehart et al, 2001), casting doubt on their findings.…”
mentioning
confidence: 99%
“…Many studies addressed this question with movement assessment batteries with normative percentiles for performance and objective scoring: for example, the PANESS (Dowell et al, 2009;Dziuk et al, 2007;Floris et al, 2016;Jansiewicz et al, 2006;Mostofsky, Burgess, & Gidley Larson, 2007), the M-ABC or M-ABC2 (Ament et al, 2015;Green, Baird et al, 2002;Green, Moore, & Reilly, 2002;Green et al, 2009;Hanaie et al, 2013;Hanaie et al, 2014;Kopp, Beckung, & Gillberg, 2010;McPhillips, Finlay, Bejerot, & Hanley, 2014;Miyahara et al, 1997;Sumner et al, 2016;Whyatt & Craig, 2012), or the Bruininks-Oseretsky test (Dewey et al, 2007;Ghaziuddin & Butler, 1998;Hilton, Zhang, Whilte, Klohr, & Constantino, 2012;Pan, 2014). These measures yield total scores which were sometimes analysed alone, but they each assess a range of fine and gross motor skills, including balance and gait, hopping or jumping, repetitive sequential movements of the hands and feet, manual dexterity and ball skills (catching and throwing).…”
mentioning
confidence: 99%